Teacher Difficulties in Teaching English to Young Learners - Imelda Telaumbanua (EDUPEDIA Publisher, 2024)
This research aims to describe the difficulties in teaching speaking to young students faced by English teachers and how teachers overcome difficulties in teaching speaking to young students. The method used in this research is qualitative. The technique used to collect data in this research is a qualitative method. To analyze the data, researchers used descriptive analysis techniques. It can be concluded that teachers face many difficulties when teaching young students to speak, but teachers can overcome these difficulties by using appropriate solutions to overcome these difficulties and by creating fun, active and creative learning